(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2024)
Cat fish is one of the top commodities that has a high nutritional content and is widely grown in South Sulawesi, based on the quantity of fisheries produced in the cultivated fisheries in the South, lele one of freshwater fish grown with high yields. The aim of this study was to determine the quality changes of fresh cat fish (Clarias gariepinus) from conventional cultivation based on chemical parameters during cold storage. The sampling technique used is Accidental Sampling, where samples are taken directly from the cultivation site. Samples have a uniform size and physical condition that still looks fresh. In this study, chilled samples used ice in a 1:1 ratio with storage times of 0 hours, 4 hours, 8 hours and 12 hours. The relationship between the storage length and the measured parameters is analyzed using simple linear regression. The results of the study showed that the pH, TVB, peroxide, organoleptic and temperature numbers had a significant relationship with storage time. Change in the quality of fish during storage 0 hours, 4 hours, 8 hours and 12 hours showed an average pH value of 6,5-6,0, TVB 5,48-18,53, peroxid number 3,39-34,63, organoleptic 9,00-7,67 and fish temperature of 16,50-21,53. Each parameter indicates that lele fish at storage from 0 hours to 12 hours still has good quality and is worthy of consumption. LoA_Kor